Analysis of Factors Related to Employee Behavior in Implementing Patient Safety Program at Insan Permata Woman and Child Hospital Tangerang - Fransisca, Martha; Darmawan, Ede Surya (Journal of Indonesian Health Policy and Administration, 2018)
Insan Permata Woman and Child Hospital was facing Patient Safety Incidence especially for periode of mid to late 2016 there were 12 incidents and 11 phlebitis cases. This indicated a gap between the conditions in the field and the ideal situation that should be achieved. This study aimed to see how the behavior of employees in implementing patient safety program and the factors that influence it. The sample of this study were 151 respondents as sample, consist of health and non health workers. The patient safety program focused on the accuracy of patient identification, reduction of risk of infection and reduction of risk of falling patients. This research was a quantitative research followed by qualitative method. The results showed that most employees already had good patient safety behavior, age and attitude were the most affecting factors in patient safety behavior. The lack of socialization of accreditation and patient safety, poor monitoring and some incomplete facilities should became the concern for the hospital as it was considered to have great influences in the daily implementation of patient safety program.